2023
DOI: 10.1097/sap.0000000000003327
|View full text |Cite
|
Sign up to set email alerts
|

Selective Repair of Motor Branches in the Femoral Nerve by Transferring the Motor Branches of Obturator Nerve

Abstract: Background Anterior branch of the obturator nerve transfer has been proven as an effective method for femoral nerve injuries, but the patient still has difficulty in rising and squatting, up and downstairs. Here, we presented a novel neurotization procedure of selectively repairing 3 motor branches of the femoral nerve by transferring motor branches of the obturator nerve in the thigh level and assessing its anatomical feasibility. Methods Eight adult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In all reanimation procedures, remarkably in CFNG, the axonal load plays a crucial role. To further investigate axon capacity in CFNG procedures, we compared our findings with relevant studies that provided data on donor and recipient nerves (Table 3) [30][31][32]. [32] Gracilis branch, obturator nerve 598 ± 83 [31] For cross-facial nerve grafts, a capacity greater than 900 donor axons was identified as a promising indicator for favorable outcomes in midfacial reanimation using free muscle grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all reanimation procedures, remarkably in CFNG, the axonal load plays a crucial role. To further investigate axon capacity in CFNG procedures, we compared our findings with relevant studies that provided data on donor and recipient nerves (Table 3) [30][31][32]. [32] Gracilis branch, obturator nerve 598 ± 83 [31] For cross-facial nerve grafts, a capacity greater than 900 donor axons was identified as a promising indicator for favorable outcomes in midfacial reanimation using free muscle grafts.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate axon capacity in CFNG procedures, we compared our findings with relevant studies that provided data on donor and recipient nerves (Table 3) [30][31][32]. [32] Gracilis branch, obturator nerve 598 ± 83 [31] For cross-facial nerve grafts, a capacity greater than 900 donor axons was identified as a promising indicator for favorable outcomes in midfacial reanimation using free muscle grafts. Furthermore, Terzis et al observed a correlation between donor axonal input and the axon numbers at the distal end of the nerve graft.…”
Section: Discussionmentioning
confidence: 99%